Modeling of HCHO and CHOCHO at a semi-rural site in southern China during the PRIDE-PRD2006 campaign - X. Li; Rohrer, F.; Brauers, T.; Hofzumahaus, A.; Lu, K.; Shao, M.; Zhang, Y. H.; Wahner, A. (Atmospheric Chemistry and PhysicsAtmospheric Chemistry and PhysicsAtmospheric Chemistry and Physics, 2014)
HCHO and CHOCHO are important trace gases in the atmosphere, serving as tracers of VOC oxidations. In the past decade, high concentrations of HCHO and CHOCHO have been observed for the Pearl River Delta (PRD) region in southern China. In this study, we performed box model simulations of HCHO and CHOCHO at a semi-rural site in the PRD, focusing on understanding their sources and sinks and factors influencing the CHOCHO to HCHO ratio (R-GF). The model was constrained by the simultaneous measurements of trace gases and radicals. Isoprene oxidation by OH radicals is the major pathway forming HCHO, followed by degradations of alkenes, aromatics, and alkanes. The production of CHOCHO is dominated by isoprene and aromatic degradation; contributions from other NMHCs are of minor importance. Compared to the measurement results, the model predicts significant higher HCHO and CHOCHO concentrations. Sensitivity studies suggest that fresh emissions of precursor VOCs, uptake of HCHO and CHOCHO by aerosols, fast vertical transport, and uncertainties in the treatment of dry deposition all have the potential to contribute significantly to this discrepancy. Our study indicates that, in addition to chemical considerations (i.e., VOC composition, OH and NOx levels), atmospheric physical processes (e.g., transport, dilution, deposition) make it difficult to use the CHOCHO to HCHO ratio as an indicator for the origin of air mass composition.
Keywords: aerosol; air-pollution sources; formaldehyde measurements; global-scale; glyoxal; max-doas measurements; organic-compounds; pearl river delta; rural site; secondary sources